The objects definition for domains management - Малахов, Евгений Валериевич; Становский, Александр Леонидович (Eastern-European Journal of Enterprise Technologies, 2012)
The objects definition problem for influence direction at subject domains management is considered. Typification of the objects characterising subject domain, for the quantity minimisation of the objects getting under operating influence is entered